Integrasi Mitos Candi Pancurawis dalam Model Green Science Learning untuk Mengembangkan Sikap Peduli Lingkungan Anak Usia Dini - Mashinta Sulistyani, Anggraeni; Prasetyo, Herry; Nuzul Islamiyati, Rizka; Alimuddin, Johar; Prasetyono, Rizki (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to examine the effectiveness of the Green Science Learning model integrated with the local wisdom values of the Pancurawis Temple myth in developing environmental care attitudes among early childhood students. The research was conducted at TK Masyitoh Miftahul Huda Langkap, Bumiayu District, during the even semester of the 2024/2025 academic year using a quasi-experimental design with a nonequivalent control group design. The research subjects consisted of two groups: an experimental group that utilized Green Science Learning oriented toward the Pancurawis Temple myth, and a control group that used conventional learning methods. The research instrument was an observation sheet measuring children's environmental care attitudes. The results showed a significant difference between the experimental and control groups (t = 4.927, p < 0.05). The mean score of the children’s environmental care attitude in the experimental group was higher (M = 84.60) than that of the control group (M = 69.80), with an effect size of 2.03 (categorized as very large). These findings confirm that integrating local wisdom values into the Green Science Learning model is effective in fostering environmental care attitude from an early age.